First PCR-free electrochemical bioplatform for the detection of mustard Sin a 1 protein as a potential “hidden” food allergen - Gamella, Maria (2022)
A disposable electrochemical PCR-free biosensor for the selective detection of a fragment encoding the protein Sin a 1, a 2S albumin considered a diagnostic marker for sensitization to mustard, is reported. The methodology is based on the formation of DNA/RNA heterohybrids by sandwich hybridization of a specific fragment of the Sin a 1 allergen coding sequence with appropriately designed RNA probes. Labeling with commercial antibodies specific to the heteroduplexes and secondary antibodies conjugated with horseradish peroxidase (HRP) was carried out onto the surface of magnetic beads (MBs). Amperometric transduction was undertaken on screen-printed electrodes using H2O2 as enzyme substrate and hydroquinone (HQ) a redox mediator. The electrochemical biosensor allows the simple and fast detection (75 min) of Sin a 1 reaching a limit of detection of 3 pM. The bioplatform was successfully applied to the analysis of the targeted Sin a 1 gene specific region using just 50 ng of non-fragmented denatured genomic DNA extracted from yellow mustard seeds.